Inverse association between Helicobacter pylori and inflammatory bowel disease: myth or fact? - Kayali, Stefano; Gaiani, Federica; Manfredi, Marco; Minelli, Roberta; Nervi, Giorgio; Nouvenne, Antonio; Leandro, Gioacchino; Di Mario, Francesco; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background: Inflammatory bowel diseases (IBD), are chronic, relapsing-remitting diseases of the gastrointestinal tract, including Crohn’s disease (CD), Ulcerative colitis (UC) and Unclassified IBD (IBDU). Their pathogenesis involves genes and environment as cofactors in inducing autoimmunity; particularly the interactions between enteric pathogens and immunity is being studied. Helicobacter pylori (HP) is common pathogen causing gastric inflammation. Studies found an inverse prevalence association between HP and IBD, suggesting a potential protecting role of HP from IBD. Methods: A literature search of the PubMed database was performed using the key words ‘’helicobacter pylori’’, ‘’inflammatory bowel disease’’, ‘’crohn disease’’, “ulcerative colitis”. Embase, Medline (OvidSP), Web of Science, Scopus, PubMed publisher, Cochrane and Google Scholar were also searched. Prevalence rate-ratios among HP in IBD patients, HP in CD patients, HP in UC patients, HP in IBDU patients were extracted, each group was compared with controls, to verify the inverse association between HP and IBD prevalence. Results: In all groups the dispersion of data suggested an inverse association between IBD group and controls, even when the comparison was carried out separately between each group of newly diagnosed patients and controls, to rule out the possible bias of ongoing pharmacologic therapy. Conclusions: The results of this review show a striking inverse association between HP infection and the prevalence of IBD, independently from the type of IBD considered across distinct geographic regions. Anyway, data should be interpreted cautiously, as wider, prospective and more homogeneous research on this topic are awaited, which could open new scenarios about environmental etiology of IBD.